CKAP4 and PLOD2 as novel prognostic biomarkers in hepatocellular carcinoma: a proteomics-driven risk stratification model - Qiulong Lu; Zhao Cao; Yueting Xiong; Junqiang Huang; Huan Zeng; Zhijian Chen; You Shu; Yahan Tan; Xiaoling Long; Xiaohui Liu; Hong Shu (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe prognosis of patients with hepatocellular carcinoma (HCC) is a research hotspot. This study aimed to identify novel prognostic protein markers for HCC using data-independent acquisition mass spectrometry (DIA-MS) and develop an integrative predictive model to enhance clinical decision-making and patient stratification.MethodsDIA-MS were implemented to identify valuable prognostic HCC biomarkers in 31 patients with different prognoses. A prognostic model was developed and validated using immunohistochemistry (IHC).ResultsCytoskeleton-associated membrane protein 4 (CKAP4) and procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 (PLOD2) were identified as key prognostic proteins, with higher expression levels associated with poor prognosis. Immunohistochemical validation confirmed the prognostic value of CKAP4 and PLOD2. A nomogram incorporating AJCC stage and the combination of CKAP4 and PLOD2 demonstrated superior predictive Sability for overall survival (OS) compared to individual indicators. The model predicted an outcome with a concordance index (C-index) of 0.738 (95% CI, 0.698–0.779) and significantly stratified patients into distinct risk groups (P < 0.001).ConclusionIn conclusion, this study identified CKAP4 and PLOD2 as novel prognostic protein markers for HCC. The developed nomogram, integrating these molecular markers with AJCC stage, shows promise in predicting OS and stratifying risk in HCC patients.